Answer:
x = 60/83
Explanation:
Solve for x:
10 - (83 x)/6 = 0
Put each term in 10 - (83 x)/6 over the common denominator 6: 10 - (83 x)/6 = 60/6 - (83 x)/6:
60/6 - (83 x)/6 = 0
60/6 - (83 x)/6 = (60 - 83 x)/6:
(60 - 83 x)/6 = 0
Multiply both sides of (60 - 83 x)/6 = 0 by 6:
(6 (60 - 83 x))/6 = 6×0
(6 (60 - 83 x))/6 = 6/6×(60 - 83 x) = 60 - 83 x:
60 - 83 x = 6×0
0×6 = 0:
60 - 83 x = 0
Subtract 60 from both sides:
(60 - 60) - 83 x = -60
60 - 60 = 0:
-83 x = -60
Divide both sides of -83 x = -60 by -83:
(-83 x)/(-83) = (-60)/(-83)
(-83)/(-83) = 1:
x = (-60)/(-83)
Multiply numerator and denominator of (-60)/(-83) by -1:
Answer: x = 60/83